In situ ruminal degradation characteristics of dry matter and crude protein from dried corn, high-protein corn, and wheat distillers grains. Issue 1 (December 2016) - Lee, Y.; Ahmadi, F.; Choi, D.; Kwak, W.
Abstract Background The continuing growth of the ethanol industry has generated large amounts of various distillers grains co-products. These are characterized by a wide variation in chemical composition and ruminal degradability. Therefore, their precise formulation in the ruminant diet requires the systematic evaluation of their degradation profiles in the rumen. Methods Three distillers grains plus soluble co-products (DDGS) namely, corn DDGS, high-protein corn DDGS (HP-DDGS), and wheat DDGS, were subjected to anin situ trial to determine the degradation kinetics of the dry matter (DM) and crude protein (CP). Soybean meal (SBM), a feed with highly degradable protein in the rumen, was included as the fourth feed. The four feeds were incubated in duplicate at each time point in the rumen of three ruminally cannulated Hanwoo cattle for 1, 2, 4, 6, 8, 12, 24, and 48 h. Results Wheat DDGS had the highest filterable and soluble A fraction of its DM (37.2 %), but the lowest degradable B (49.5 %;P < 0.001) and an undegradable C fraction (13.3 %;P < 0.001). The filterable and soluble A fraction of CP was greatest with wheat DDGS, intermediate with corn DDGS, and lowest with HP-DDGS and SBM; however, the undegradable C fraction of CP was the greatest with HP-DDGS (41.2 %), intermediate with corn DDGS (2.7 %), and lowest with wheat DDGS and SMB (average 4.3 %). The degradation rate of degradable B fraction (% h−1 ) was ranked from highest to lowest as follows for 1) DM: SBM (13.3), wheat DDGS (9.1), and corn DDGS and HP-DDGS (average 5.2); 2) CP: SBM (17.6), wheat DDGS (11.6), and corn DDGS and HP-DDGS (average 4.4). Thein situ effective degradability of CP, assuming a passage rate of 0.06 h−1, was the highest (P < 0.001) for SBM (73.9 %) and wheat DDGS (71.2 %), intermediate for corn DDGS (42.5 %), and the lowest for HP-DDGS (28.6 %), which suggests that corn DDGS and HP-DDGS are a good source of undegraded intake protein for ruminants. Conclusions This study provided a comparative estimate of ruminal DM and CP degradation characteristics for three DDGS co-products and SBM, which might be useful for their inclusion in the diet according to the ruminally undegraded to degraded intake protein ratio.